Egg capsules, eggs and embryos of the southwestern Atlantic gastropod Coronium coronatum (Gastropoda: Muricidae) - Pastorino, G. (2007)
The egg capsules, eggs and embryos of the muricid gastropod Coronium coronatum are described for the first time. Capsules are sessile, bulliform, semi-circular, with a plug in the dorsal center. Sutures split the capsule into two asymmetrical halves. Recently laid capsules showed the presence of 3639 (n = 2) uncleaved nurse eggs with a diameter of 180-210 μm (mean = 197.4 ± 8.9). The number of early embryos was 9-11. The size of the embryos was 320 × 320 to 820-880 μm. Nine pre-hatching embryos of 3.94 mm (n = 8, SD = 0.32) were found inside the older capsule. SEM illustrations of embryos and radulae are provided. Comparison of shell and radula of embryos with the protoconch and radulae of adults of C. coronatum revealed that the capsule belongs to this species. © The Author 2007. Published by Oxford University Press on behalf of The Malacological Society of London, all rights reserved.